The family and its problems in andragogical magazines of the late fifties and early sixties of the twentieth century - Janik-Komar, Joanna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The text deals with the family problems and its support for their solutions based on articles published in andragogical magazines of the late fifties and early sixties of the twentieth century. These issues are extremely interesting, since they relate to the family life culture, marriage preparation and family life education. Preparing for marriage is of great importance for the future of its operation. Its absence has an effect on family problems and marital conflicts later in life. Parenting universities provided support for families in solving their problems, primarily in dealing with behavioral problems, but also provided knowledge from other areas of life.
Keywords: family; marriage preparation; family crisis; parenting university; magazines; andragogica